2022
DOI: 10.3846/mma.2022.14043
|View full text |Cite
|
Sign up to set email alerts
|

Functional Modelling of Telecommunications Data

Abstract: This work deals with statistical modeling and forecasting of telecommunications data. Main mobile traffic events (SMS, Voice calls, Mobile data) are smoothed using B-spline functions and later analyzed in a functional framework. Functional linear auto-regression models are fitted using both bottom-up and topdown design methodologies. The advantages and disadvantages of both approaches for the prediction of mobile telephone users’ habits are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…For the case study, voice consumption in minutes and mobile data consumption in MB are used. This type of date was analyzed in [20] using first-order auto-regressive models, and it was confirmed that models of type (1) are appropriate.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…For the case study, voice consumption in minutes and mobile data consumption in MB are used. This type of date was analyzed in [20] using first-order auto-regressive models, and it was confirmed that models of type (1) are appropriate.…”
Section: Introductionmentioning
confidence: 75%
“…In order to perform the test on real data, we employed a telecommunications data set. The data set was used by Birbilas and Račkauskas [20], who showed that the FAR(1) model is appropriate for prediction purposes. In this work, we continue the analysis of this data set by proposing a test for the detection of structural changes.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The voice tra c has been calculated from the Erlang formula. The required number of channels was obtained by Erlang B formula for a given block probability and a predicted value of tra c [26], [27] Where P B is the blocking probability, a is the predicted tra c in Erlang, n is the number of channels.…”
Section: Methodsmentioning
confidence: 99%